Cracking the GRE with four complete sample tests on CD-ROM - Lurie, Karen (Tp.HCM : Nxb Trẻ, 2001)
Nội dung sách gồm bốn phần: Orientation; How to crack the verbal section; How to crack the math section; How to crack the analytic section; How to crack the optional writing sample; Practice Sets.
Keywords: Anh ngữ; Anh ngữ